2004
DOI: 10.1210/en.2003-1327
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Type Plasminogen Activator and Its Inhibitor Plasminogen Activator Inhibitor Type 1 Are Coordinately Expressed during Ovulation in the Rhesus Monkey

Abstract: Ovulation is a gonadotropin-controlled process that is essential for the propagation of all mammalian species. In the present study, we used a pregnant mare serum gonodotropin/human chorionic gonadotropin (hCG)-induced, synchronized ovulation model in rhesus monkeys and systematically investigated the roles of the plasminogen activator (PA) system in the ovulatory process of the primate. At different follicular developmental stages throughout the periovulatory period, samples of ovaries, granulosa cells, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…mRNA for plasminogen activator inhibitor-1 (PAI-1) has been found in the thecal and stromal tissue surrounding the follicle with its highest expression occurring 6 h prior to ovulation (Ny et al 1993). PAI is localised to the theca interna in the rat (Hasan et al 2002) and monkey (Liu et al 2004) ovary and to the granulosa and theca cells in the human ovary (Atiomo et al 2000) and co-localises with aHSPG in the ovulated follicle (Hasan et al 2002).…”
Section: Heparan Sulphate Proteoglycansmentioning
confidence: 99%
“…mRNA for plasminogen activator inhibitor-1 (PAI-1) has been found in the thecal and stromal tissue surrounding the follicle with its highest expression occurring 6 h prior to ovulation (Ny et al 1993). PAI is localised to the theca interna in the rat (Hasan et al 2002) and monkey (Liu et al 2004) ovary and to the granulosa and theca cells in the human ovary (Atiomo et al 2000) and co-localises with aHSPG in the ovulated follicle (Hasan et al 2002).…”
Section: Heparan Sulphate Proteoglycansmentioning
confidence: 99%
“…At the early stage of CL development (3-5 d after hCG injection), uPA, but not tPA, is the only active PA species that is identified in the CL. However, during luteolysis when serum progesterone levels and StAR mRNA expression in the CL declined dramatically on D13 after hCG injection [33] , a substantial elevation in tPA mRNA, which is in agreement with corresponding increased tPA activity [14] , was observed, implying that tPA might be a luteolytic factor. Most interesting of all, just prior to the increment of both tPA mRNA and activity levels in the monkey CL at the time of initiation of luteolysis, a peak level of PAI-1 mRNA was measured.…”
Section: Discussionmentioning
confidence: 73%
“…In our previous studies, using a PMSG / hCG induced luteinized rhesus monkey model, we have demonstrated the involvement of PA/PAI-1 system in controlling CL development [14,33] . At the early stage of CL development (3-5 d after hCG injection), uPA, but not tPA, is the only active PA species that is identified in the CL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of PA, tissue-type PA (tPA) and urokinase-type PA (uPA), and a PA inhibitor, PAI-1, have been reported in rat [4] and monkey [5] ovaries. Our previous studies have demonstrated that GCs and oocyte of rat and rhesus monkey produced tPA, while theca cells produced PAI-1, the coordinated expression of tPA and PAI-1 regulated by gonadotrophins in the ovary-induced ovulation [6,7]. Evidence has also shown that rat GCs in vitro express tPA in response to FSH, LH, GnRH, VIP, and growth factors via different signaling pathways [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%